Phenolic compounds and squalene in olive oils: the concentration and antioxidant potential of total phenols, simple phenols, secoiridoids, lignansand squalene - Owen, Robert; Mier, Walter; Hull, William Edmund; Spiegelhalder, Bertold; Bartsch, Helmut (Food and chemical toxicology, 2000)
The aim of this study was to evaluate the phenolic antioxidant and squalene content in a range of olive and seed oils. A mean of 290 ± 38 (SEM) mg squalene/100 g was detected. However, while there was a weak significant difference between extra virgin (424 ± 21 mg/kg) and refined virgin (340 ± 31 mg/100 g; P<0.05) olive oils, highly significant differences were evident between extra virgin olive oils (P<0.0001) refined virgin olive oils (P<0.0001) and seed oils (24 ± 5 mg/100 g). While seed oils were devoid, on average, the olive oils contained 196 ± 19 mg/kg total phenolics as judged by HPLC analysis, but the value for extra virgin (232 ± 15 mg/kg) was significantly higher than that of refined virgin olive oil (62 ± 12 mg/kg; P<0.0001). Appreciable quantities of simple phenols (hydroxytyrosol and tyrosol) were detected in olive oils, with significant differences between extravirgin (41.87 ± 6.17) and refined virgin olive oils (4.72 ± 215; P<0.01). The major linked phenols were secoiridoids and lignans. Although extra virgin contained higher concentrations of secoiridoids (27.72 ± 6.84) than refined olive oils (9.30 ± 3.81) this difference was not significant. On the other hand, the concentration of lignans was significantly higher (P<0.001) in extra virgin (41.53 ± 3.93) compared to refined virgin olive oils (7.29 ± 2.56). All classes of phenolics were shown to be potent antioxidants. In future epidemiologic studies, both the nature and source of olive oil consumed should be differentiated in ascertaining cancer risk.